Fragile Statistical Findings in Randomized Controlled Trials Evaluating Autograft Versus Allograft Use in Anterior Cruciate Ligament Reconstruction: A Systematic Review - Megafu, Michael; Megafu, Emmanuel; Mian, Hassan; Singhal, Sulabh; Lee, Alexander; Gladstone, James N.; Parisien, Robert L. (Arthroscopy, 2024)
To analyze the statistical stability of randomized controlled trials (RCTs) evaluating the surgical management of autografts versus allografts in the anterior cruciate ligament reconstruction (ACLR) literature and calculate the fragility index (FI) and fragility quotient and explore a subgroup analysis by calculating the proportion of outcome events where the FI was less than the number of patients lost to follow-up. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we conducted a systematic search in the PubMed and Cochrane databases to identify RCTs published between 2000 and 2022 that investigated the use of autografts versus allografts in ACLR literature and reported dichotomous data. The fragility index of each dichotomous variable was calculated through the reversal of a single outcome event until significance was reversed. The fragility quotient was calculated by dividing each fragility index by the study sample size. The interquartile range also was calculated. Of the 4407 articles screened, 23 met the search criteria, with 11 RCTs evaluating ALCR using autografts and allografts included for analysis. Two hundred and 18 outcome events with 32 significant (P < .05) outcomes and 186 nonsignificant (P ≥ .05) outcomes were identified. The overall fragility index and fragility quotient for all 218 outcomes were 6 subjects (interquartile range 5-8) and 0.058 (interquartile range 0.039-0.077). Fragility analysis of statistically significant outcomes and nonsignificant outcomes had a fragility index of 3.5 (interquartile range 1-5.5) and 6 (interquartile range 5-8), respectively. All of the studies reported a loss to follow-up where 45.5% (5) reported a loss to follow-up greater or equal to 6. The RCTs in the ACLR peer-reviewed literature evaluating autograft versus allograft use are vulnerable to a small number of outcome event reversals and exemplify significant statistical fragility in statistically significant findings. Level I, systematic review of Level I studies.